Public Opinions in Contemporary Vietnam Digital Newspapers. Case Study: Vnexpress and Tuổi Trẻ Digital Newspapers - Kien, Phan Van (Journal of Ecohumanism, 2024)
Journalism and politics are intertwined in Vietnam and throughout the globe. This assumption is evident in Vietnam, where newspapers are viewed as political instruments of the party that educate and inform the public about national policies and national will. In the era of social media, where non-state media and anyone with a smartphone and social network account can express their opinions on social issues, the objectives of state-run newspapers have been profoundly challenged. In 2011, the politburo added a new objective for journalism in Vietnam, which is to criticize social issues for the general public. This paper examines the relationship between the three fundamental actors in the Vietnamese mediascape: newspapers, audiences, and the state. From the two case studies of the Vietnamese newspapers Vnexpress and Tuổi Trẻ, the mechanism of contemporary Vietnamese public opinion will be uncovered.